EMERGING BALINESE FRANCHISED CITY HOTELS IN LEGAL CONTEXTS: TOWARD MODEL PROVISIONS OF LOCAL GOVERNMENT REGULATION AND A SELF-REGULATION FRAMEWORK - Dharmawan, Ni Ketut Supasti; Salain, Made Suksma Prinjandhini; Hallewell, Benjamin (Indonesia Law Review, 2018)
The existence of traditionally managed Balinese city hotels is increasingly threatened by the presence of chain hotels, which are internationally managed with an excellent standard of hotel hospitality. In a commercial context, franchised hotels benefit the franchisor, franchisee, and consumers in terms of the quality of hotel standardization and reputation. Still, such hotels remain incomparable to the Balinese city hotels managed traditionally by family owners. In the legal context, the emergence of various types of modern franchised city hotels in Bali is influenced by suitable laws and policies, such as the World Trade Organization (WTO) Agreement with one of its ground bases called the “Non-Discrimination Principle” at the international level and at the regional level, the Association of Southeast Asian Nations Economic Community, which also emphasizes that one of the important central pillars of the multilateral trading system is a region fully integrated into the global economy. The emergence of modern chain city hotels has prevented the local city hotels from competing in terms of both the infrastructure and quality management services. To overcome these crucial issues, the model provisions of the local government regulation and self- regulation framework of hotel associations must be constructed to strengthen the local city hotels as chain hotels by implementing traditional values, e. g. , the Tri Hita Karana, the corporate social responsibility as a strategic development, and human rights approaches, that comply with the WTO Agreement and the laws and policies at the regional level.